Development of a squash variety (Cucurbita argyrosperma Huber) for seed production through participatory breeding - Ronicke, Stephan; Carrillo-Ávila, Eugenio; Monsalvo-Espinosa, José A.; Carmona-Arellano, Mauricio; Silva-Rojas , Hilda V.; Poot-Dzib , Juan A.; Arreola-Enríquez, Jesús; Nava-Díaz , Cristian; Pérez-Rodríguez, Paulino; Osnaya-González , Mónica (Agro-Divulgación, 2023)
The "Chihua" squash (Cucurbita argyrosperma Huber) is used to obtain "pepita" seeds, which are important in the preparation of dishes, sweets, snacks and oils. In Campeche, Mexico, it is the fourth crop in planted area, however, there are no improved varieties. Producers use their own seed, so they have low yields and pest and disease problems, among others. Currently, an improved variety is being developed in a participatory manner with producers for the region, to increase yield and improve biotic and abiotic stress. The progress in the variety breeding is presented.